Efectos fisiológicos del hábito de la coca. Una aproximación histórica durante el siglo XX - Ayala Pío, Salomón (2024)
The objective of this study is to offer a historical perspective of the academic research about the physiological effects of the chewing of coca leaves during the twentieth century. We reviewed papers in old journals and recent publications, related to the stimulant, mitigating effects of fatigue and its action on work capacity. We reviewed the studies of Gutiérrez-Noriega during the 40s and the experimental demonstration of increase of locomotor activity with coca and cocaine. The studies have not elucidated the influence   on work capacity of the coca users.